Overview of the Level of Knowledge of Posyandu Cadres about Monitoring the Growth of Toddler Development - Irmawati, Irmawati; Amin, Kurniawan; Haruna, Sri Rahmah (Omni Health Journal, 2024)
Background: Posyandu cadres are community leaders who are willing, able and have time to carry out posyandu activities and are tasked with helping the smooth running of health services so that one of the most basic posyandu problems is the low level of knowledge of cadres both from an academic and technical side. Objective: It is known that the level of knowledge of posyandu cadres about understanding, assessing, monitoring the growth of toddler development in Camba-Camba Village, Jeneponto Regency Methods: The research method used was quantitative research with a descriptive design conducted on 35 samples of posyandu cadres in the working area of the Togo-Togo Health Center, Camba-Camba Village, Jeneponto Regency with a total sampling technique Conclusion: From the results of the study, it can be concluded that  most respondents have a level of knowledge about the understanding of growth in the development of the category of less than 15 (41.7%) people, monitoring the growth of development in the good category as many as 17 (47.2%) and less as many as 3 (8.3%) people, assessment of the growth of development in the good category as many as 15 (41.7%) people.